1987
DOI: 10.1002/ijc.2910390512
|View full text |Cite
|
Sign up to set email alerts
|

Antibody protein dose and radioimmunodetection of gw‐39 human colon tumor xenografts

Abstract: This study investigates the influence of antibody protein dose on the radioimmunodetection of a CEA-producing, human colonic tumor xenograft (GW-39) using affinity-purified goat anti-carcinoembryonic antigen (CEA) antibody and a murine monoclonal anti-CEA antibody (NP-2). Hamsters bearing GW-39 tumors were given an equal mixture of 131I-labelled antibody and 125I-labelled irrelevant IgG at doses varying from 0.01 to 1.0 mg (0.1 to 10 mg/kg body weight) for each antibody preparation. No differences were found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Hence, it appears that large tumors may en trap macromolecules, including immunoglob ulins, more than normal tissues, as already observed by Duran-Reynals [60] over half a century ago. On the basis of autoradiographic results, we believe that this phenomenon is related to the increased number of necrotic cells in larger tumors, particularly in the less well-vascularized core, which would inhibit the efflux of macromolecules from tumors [61], This is indeed consistent with the find ings in one of our very first studies of tumor imaging in the hamster model bearing the 66 Goldenberg CEA as a Target Antigen for RAID and RAIT GW-39, CEA-producing tumor, where we ob served the nonspecific accretion of normal IgG in large, but not in small tumors [9], and with our clinical observation that large tu mors show increased accretion of radiola beled normal IgG, whereas small tumors only show uptake of a radiolabeled CEA antibody [62], Later, Moshakis et al [63] showed that as tumor size progressively decreased in nude mice, the percent of injected dose per gram localized in the tumors increased exponen tially, which was also observed by us in the GW-39 human tumor xenograft model [64,65], These findings suggest that foci of small tumors, even micrometastatic lesions, would be highly accessible to antibody present in the extravascular compartment, and would in fact accrete a relatively high amount of the specific antibody. The absorbed radiation dose is a function of the energy deposited per gram of tissue.…”
Section: Prospects For Radioimmunotherapy (Rait)mentioning
confidence: 57%
See 1 more Smart Citation
“…Hence, it appears that large tumors may en trap macromolecules, including immunoglob ulins, more than normal tissues, as already observed by Duran-Reynals [60] over half a century ago. On the basis of autoradiographic results, we believe that this phenomenon is related to the increased number of necrotic cells in larger tumors, particularly in the less well-vascularized core, which would inhibit the efflux of macromolecules from tumors [61], This is indeed consistent with the find ings in one of our very first studies of tumor imaging in the hamster model bearing the 66 Goldenberg CEA as a Target Antigen for RAID and RAIT GW-39, CEA-producing tumor, where we ob served the nonspecific accretion of normal IgG in large, but not in small tumors [9], and with our clinical observation that large tu mors show increased accretion of radiola beled normal IgG, whereas small tumors only show uptake of a radiolabeled CEA antibody [62], Later, Moshakis et al [63] showed that as tumor size progressively decreased in nude mice, the percent of injected dose per gram localized in the tumors increased exponen tially, which was also observed by us in the GW-39 human tumor xenograft model [64,65], These findings suggest that foci of small tumors, even micrometastatic lesions, would be highly accessible to antibody present in the extravascular compartment, and would in fact accrete a relatively high amount of the specific antibody. The absorbed radiation dose is a function of the energy deposited per gram of tissue.…”
Section: Prospects For Radioimmunotherapy (Rait)mentioning
confidence: 57%
“…However, this is not true for IgG frag ments, which can show tumor targeting and clearance from normal tissues within a few hours [3,45]. Although conjugation of 99mTc to whole IgG has permitted tumor imaging at 24 h [46], earlier imaging can be accom plished with the use of Fab', for example with 64 Goldenberg CEA as a Target Antigen for RAID and RAIT in 4 h [3,41,[47][48][49]. Using a recently devel oped simple and direct Fab' labeling kit for 99mTc [50,51], we and others have demon strated that very small colorectal tumors, in cluding those in the liver, can show 'hot' or rimmed images within a few hours of injection of the radiolabeled agent [3,41,[47][48][49]52], A multicenter trial of this imaging kit in colorec tal cancer patients showed that tumors as small as 0.5-1.0 cm could be disclosed, that the kit is safe (rarely evoking HAMAs after a single application), and is particularly effective in detecting tumors in the liver [53,54].…”
Section: Current Status Of Cea Raidmentioning
confidence: 99%
“…The results indicate that tumor size at time of treatment is critical and that, to cause remission of bigger (.0.3 cm3) tumors, larger doses are required than were administered in most studies, including our own. In the study that had comparable tumor remission frequencies for both small and large tumors (3,11), the tumor dose to large tumors was 3-fold (7200 rad) that received by small tumors (2400 rad). In none of the other reported studies with comparable sized, or larger tumors, did tumor dose approach this level (4,5,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Other difficulties in targeting large tumors include the observation that small tumors have a greater fractional uptake of the administered dose of mAb per unit mass of tumor than do large tumors (3,35). Additionally, larger quantities of mAbs may be needed to effect tumor saturation in large tumors than in small ones (20), and small tumors, in general, are more radiosensitive than large tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation